2019
DOI: 10.1016/j.ecss.2019.106307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surf zone zooplankton dynamics in a Southwestern Atlantic sandy beach: Seasonal cycle and tidal height influence

Abstract: Surf zones of sandy beaches are poorly studied in comparison to estuarine and continental shelf waters, specifically because of the difficulties experienced in sampling in high-energy environments. The zooplankton of these areas, therefore, has received less

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…This was supported by the correlation analysis results between zooplankton abundance, feeding habits, and environmental factors. In addition, although the particulate organic matter content was not measured separately in this study, previous studies have confirmed that SPM can be used as a food source by copepods (Poulet, 1978;Roman, 1984;David et al, 2005;Lee et al, 2019;Meneńdez et al, 2019).…”
Section: A B Figurementioning
confidence: 77%
See 1 more Smart Citation
“…This was supported by the correlation analysis results between zooplankton abundance, feeding habits, and environmental factors. In addition, although the particulate organic matter content was not measured separately in this study, previous studies have confirmed that SPM can be used as a food source by copepods (Poulet, 1978;Roman, 1984;David et al, 2005;Lee et al, 2019;Meneńdez et al, 2019).…”
Section: A B Figurementioning
confidence: 77%
“…Although many studies have shown that SPM has a negative effect on zooplankton in estuarine ecosystems (Alcaraz et al, 1980;White and Dagg, 1989;Arendt et al, 2011;Kang, 2012), several studies have suggested that increases in SPM can have a positive effect on the population maintenance of zooplankton because of the possible nutritional benefits from organic or potential food matter adhered to the SPM (Poulet, 1978;Arruda et al, 1983;Kwon et al, 2002;Cloern et al, 2017). Therefore, SPM can be used as an alternative food source (Poulet, 1978;Roman, 1984;David et al, 2005;David et al, 2006;Lee et al, 2019;Meneńdez et al, 2019). Zooplankton have also been recognized as an indicator because they can sensitively respond to environmental changes (Dufrene and Legendre, 1997;Beaugrand, 2004;Bonnet and Frid, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In general terms, many species represented by a low number of individuals and a few dominant ones characterize the surf zone faunistic assemblages, many of them shared with nearby coastal ecosystems like estuaries (Fiori et al, 2022). Concerning the general ecology of surf-zooplankton, there are a few studies concentrated in Brazil (Avila et al, 2009;Costa et al, 2011;Oliveira-Santos et al, 2016;Pinheiro et al, 2011Pinheiro et al, , 2013Rodrigues et al, 2019), Argentina (Baleani et al, 2020(Baleani et al, , 2021Menéndez et al, 2019), USA (De Lancey, 1987;Morgan et al, 2017;Stull et al, 2016), Egypt (Aboul Ezz et al, 2014), and Portugal (Guerreiro et al, 2021). Holoplankton (organisms that spend their entire life cycle in the water column) generally dominate the surf zone waters; however, meroplankton (those with only part of their lives in the plankton) can also be relevant in terms of abundance and the number of species.…”
Section: Introductionmentioning
confidence: 99%
“…Holoplankton (organisms that spend their entire life cycle in the water column) generally dominate the surf zone waters; however, meroplankton (those with only part of their lives in the plankton) can also be relevant in terms of abundance and the number of species. Thus, surf-zooplankton is mainly represented by crustaceans, especially copepods, with larval stages of benthic adults (bivalves, cirripeds, polychaetes) and gelatinous forms as intermittent visitors and with sporadic dominance, among others (e.g., Costa et al, 2011;Guerreiro et al, 2021;Menéndez et al, 2019;Pinheiro et al, 2013). Mysidacea and benthic organisms, such as amphipods and isopods, are frequently observed (e.g., Marin Jarrin et al, 2015Jarrin et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between land and sea will form a unique morphology in each coastal area [2]- [6]. As a dynamic zone, the coastal zone does not only affect physical factors, but also biology [7], [8] and chemistry [9]. A number of parameters that can affect changes in coastal physical conditions, including: currents, waves, tides, storms, and landscapes [10]- [12].…”
Section: Introductionmentioning
confidence: 99%